Organizational and technological reliability of construction in Iraq - O. A. Pobegaylov; A. A. R. A. Al-Masri (Вестник СибАДИ)
Introduction. Capital construction of buildings and structures in the Republic of Iraq is one of the most important areas of production activity, it is the basis for the development of all sectors in the country’s economy. The modern construction complex of Iraq is constantly developing and improving, modern construction materials, technologies, methods of organization and management of construction are being introduced, which makes it possible to implement construction projects of almost unlimited complexity. However, in modern conditions that have been formed in the Republic of Iraq from the end of the 20th century to the present, a special problem has become the need for full and timely provision of construction with all types of resources, which, in the conditions of the Iraqi construction market, is an unsolved scientific and practical task, due to the high influence of negative factors different nature, thereby reducing the organizational and technological reliability of the construction of buildings. Materials and methods. To solve this problem, 7 stages of developing a system of indicators for the sustainable development of resource infrastructure, which will improve the organizational and technological reliability of construction in Iraq are proposed. In addition, a model for calculating generalized criteria for the organizational and technological reliability of construction was developed. To determine the significance of indicators of organizational and technological reliability, it is proposed to use the method of expert evaluation. Results. A system of indicators for the sustainable development of resource infrastructure has been developed, consisting of seven stages. The indicators of organizational and technological reliability of construction are singled out and their significance is determined. Discussion and conclusions. Taking into account the influence of the factors studied by us predetermines the use of the concept of risk as a quantitative measure of the implementation of a negative scenario of the construction progress under the influence of various factors, which allows further research using the apparatus of risk theory. On the basis of the proposed research method, we can calculate the effectiveness of indicators of resource provision for construction in Iraq.